The Role of Plyometric Training in Optimizing Strength and Agility - Teguh Satria; Anjario Ardiyan (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to examine the effectiveness of plyometric training in improving strength and agility, as well as to compare the extent to which plyometric exercises are more effective than conventional training methods. The research employed an experimental approach designed to identify causal relationships between the treatment and the measured outcomes. The study utilized a Pretest Posttest One Group Design, in which measurements were conducted both before and after the intervention. The research sample comprised 20 students actively participating in the volleyball extracurricular program. The research instruments included a leg dynamometer to assess lower-limb muscle strength and a zig-zag test to evaluate participants’ agility levels. The findings revealed significant differences between the pretest and posttest results for both dependent variables strength and agility. The obtained significance value of 0.000 (p < 0.05) indicates that the implemented training programs, namely the box drill and flog jump exercises, had a substantial impact on enhancing the participants’ physical performance. Therefore, it can be concluded that plyometric training has a positive influence and statistical impact on increasing strength and agility. Overall, this study reaffirms that plyometric training is an effective and efficient method for enhancing physical capabilities, making it highly recommended for inclusion in athletic conditioning and performance development programs.